Symmetrization and initial boundary-value problems for certain classes of nonlinear second order parabolic equations - Bazalii, B. V.; Tedeev, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Initial boundary-value problems are considered for equations of porous medium and $p$-Laplace types. By using the Schwarz symmetrization method, the $L_p$-estimates for the solutions of the original problems are obtained in terms of the analogous estimates for the corresponding symmetric solutions.